Manipulation of the magnetoresistance effect in a double-helix DNA. (22nd October 2018) - Li, Yao-Sheng; Wang, Xue-Feng
Abstract: Magnetoresistance ( R m ) of a double-stranded (G:C) N DNA sandwiched between ferromagnetic electrodes has been studied using the transfer matrix method of the tight-binding model. A R m magnitude up to 72.5% for DNA in its natural structure is observed when the spin–orbit coupling with the helix spring geometry and a possible dephasing effect are taken into account. It can be greatly manipulated by stress or torque applied to the DNA with respect to its axis. In addition, the external voltage bias can also be used to efficiently control R m . The dependence of R m on the DNA length in a decaying oscillation form is observed.